Effect modification of the association between vitamin B2 intake and diabetes mellitus by sex: findings from the National Health and Nutrition Examination Survey 2013–2020 - Yang, Hui; Wang, Xudong; Xi, Xiaolan; Xia, Yujia; Jiang, Mingxia; Zuo, Hui (Frontiers in Nutrition, 2024)
Background and objectivesThe relationship between vitamin intake and diabetes mellitus (DM) has attracted growing attention. Only few studies have linked vitamin B2 (VB2) and development of DM. In this study, we aimed to assess the association between VB2 intake and DM among U.S. adults.MethodsWe performed a cross-sectional analysis by using four waves of the National Health and Nutritional Examination Surveys (NHANES) data in 2013–2020. A total of 18,338 participants aged ≥18 years were included. VB2 intake was estimated by 24-h dietary recall on the first day. We used multiple logistic regression analysis to assess the association between VB2 intake and DM in men and women, separately.ResultsVB2 intake was significantly associated with DM in women but not in men (P-interaction < 0.05). In women, the multivariable-adjusted odds ratio (OR) for the fourth compared with the first quartile of VB2 intake was 0.67 (95% CI: 0.48, 0.93, P-trend = 0.025). Each standard deviation increment of log-transformed VB2 intake was associated with 19% reduced odds of DM (P = 0.005). In contrast, no significant association between VB2 intake and DM was observed in men (P-trend > 0.05). An inverse dose-response relationship between VB2 intake and DM was observed in women, but not in men.ConclusionsIncreased VB2 intake was associated with lower odds of DM in women, but not men. Our study underscores the potential role of VB2 in the prevention of DM in women. Prospective studies from different populations are warranted to confirm our findings.